2019
DOI: 10.1021/acscatal.9b01506
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of an Unnatural Deazaflavin Cofactor That Can Fuel F420-Dependent Enzymes

Abstract: F 420 -dependent enzymes are found in many microorganisms and can catalyze a wide range of redox reactions, including those with some substrates that are otherwise recalcitrant to enzyme-mediated reductions. Unfortunately, the scarceness of the cofactor prevents application of these enzymes in biocatalysis. The best F 420 -producing organism, Mycobacterium smegmatis, only produces 1.4 μmol per liter of culture. Therefore, we synthesized the unnatural cofactor FO-5′phosphate, coined FOP. The FO core-structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 50 publications
0
66
0
2
Order By: Relevance
“…The ability of the mycobacterial FDORs to reduce activated C=C double bonds was first identified when DDN was shown to be responsible for activating the bicyclic nitroimidazole PA-824 in M. tuberculosis. These enzymes were then shown to also reduce enoates in aflatoxins, coumarins, furanocoumarins and quinones [6,12,14,16,[34][35][36][37][38]. Recent studies have shown that these enzymes are promiscuous and can use cyclohexen-1-one, malachite green and a wide range of other activated ene compounds as substrates [35].…”
Section: Cofactor F420-dependent Reactions With Relevance To Biocatalmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability of the mycobacterial FDORs to reduce activated C=C double bonds was first identified when DDN was shown to be responsible for activating the bicyclic nitroimidazole PA-824 in M. tuberculosis. These enzymes were then shown to also reduce enoates in aflatoxins, coumarins, furanocoumarins and quinones [6,12,14,16,[34][35][36][37][38]. Recent studies have shown that these enzymes are promiscuous and can use cyclohexen-1-one, malachite green and a wide range of other activated ene compounds as substrates [35].…”
Section: Cofactor F420-dependent Reactions With Relevance To Biocatalmentioning
confidence: 99%
“…FGD from Rhodococcus jostii and Mycobacterium smegmatis have been studied and expressed in E. coli, both the enzymes were stable in in vitro assays [26,39,60]. Both FGDs have been expressed in engineered E. coli producing cofactor F 420 together with FDORs [38,59] FGDs have been shown to efficiently regenerate reduced cofactor F 420 both in vivo and in vitro. However, the cost of the glucose-6-phosphate and the need to separate reaction products from the accumulated FGD byproduct (6-phosphoglucono-d-lactone) may prove to be impediments for the adoption of FGD as a recycling system for cofactor F 420 in the in vitro biotransformations.…”
Section: Cofactor Recycling For Cofactor F 420mentioning
confidence: 99%
See 3 more Smart Citations